2021
DOI: 10.1016/j.redox.2021.102058
|View full text |Cite
|
Sign up to set email alerts
|

The E3 ubiquitin ligase TRIM31 is involved in cerebral ischemic injury by promoting degradation of TIGAR

Abstract: Tripartite motif (TRIM) 31 has been implicated in diverse biological and pathological conditions. However, whether TRIM31 plays a role in ischemic stroke progression is not clarified. Here we demonstrated that TRIM31 was significantly downregulated in the ischemic brain and the deficiency of TRIM31 alleviated brain injury induced by middle cerebral artery occlusion by reducing reactive oxygen species production and maintaining mitochondrial homeostasis. Mechanistically, we found that TRIM31 is an E3 ubiquitin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…After 2 h of MCAO, TIGAR reached approximately 2.29-fold ( p < 0.05) of that in sham mice. These results were in line with previous findings that TIGAR undergoes significant upregulation after cerebral ischemia [ 6 , 12 ]. Notably, NADPH, the product from glucose metabolism via the PPP, declined as the ischemia duration increased, suggesting TIGAR failed to further activate PPP to meet the demand under sustained ischemic condition ( Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…After 2 h of MCAO, TIGAR reached approximately 2.29-fold ( p < 0.05) of that in sham mice. These results were in line with previous findings that TIGAR undergoes significant upregulation after cerebral ischemia [ 6 , 12 ]. Notably, NADPH, the product from glucose metabolism via the PPP, declined as the ischemia duration increased, suggesting TIGAR failed to further activate PPP to meet the demand under sustained ischemic condition ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…In addition, glucose is predominantly metabolized by glycolysis, rather than the PPP, upon reperfusion [ 11 ]. Paradoxically, neuronal TIGAR shows a four-fold upregulation after 2 h of ischemia [ 6 ], which can be sustained as long as 24 h after ischemia in mice [ 12 ]. It remains largely unexplored whether TIGAR-NADPH may play a role in counteracting oxidation caused by prolonged cerebral ischemia.…”
Section: Introductionmentioning
confidence: 99%
“… 26 , 27 Furthermore, the PPP is the key to maintaining mitochondrial function. 28 Impaired mitochondrial function plays an essential role in allograft IRI. 29 In this study, transcriptome, proteome, and metabolome network analysis confirmed that PPP activity was stable throughout IFLT, while it was suppressed during preservation but enhanced postrevascularization in CLT.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that its rate‐limiting enzyme, glucose‐6‐phosphate dehydrogenase (G6PDH), can protect the brain and heart from IRI 26,27 . Furthermore, the PPP is the key to maintaining mitochondrial function 28 . Impaired mitochondrial function plays an essential role in allograft IRI 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Tripartite motif-containing proteins (TRIMs) are a family of E3 ubiquitin ligases and mediate endogenous proteins for degradation by the ubiquitin-proteasome system [ 23 , 24 ]. TRIMs are implicated in the pathogenesis of various human tumors, including the glioblastoma.…”
Section: Introductionmentioning
confidence: 99%